The Effects of Negative Affectivity, Hierarchical Status, and Self-Determination on Workplace Victimization - Aquino, Karl; Grover, Steven L.; Bradfield, Murray; Allen, David G. (Academy of Management Journal, 1999)
This study investigated the conditions under which employees are more or less likely to become targets of coworkers’ aggressive actions. Results from a field survey showed people high in negative affectivity more often perceived themselves as victims, as did people who were low in the self-determination component of empowerment. In addition, hierarchical status appeared to buffer the influence of negative affectivity: Negative affectivity was not related to indirect victimization for higher-status people but was positively related to indirect victimization for lower-status people.